Muhammadiyah's New Fiqh Reasoning : Constructing a Holistic Islamic Law Paradigm - Niki Alma Febriana Fauzi (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2019)
This paper attempts to trace Muhammadiyah's new fiqh reasoning in Islamic legal discourse, and its probability to become a holistic legal paradigm. In the leadership of Syamsul Anwar, Muhammadiyah through Majelis Tarjih introduced the idea of a new fiqh concept which is considered to be different from the classical fiqh concept. This fiqh reasoning has produced many tarjih products, such as Fiqh Air (Water Jurisprudence), Fikih Kebencanaan (Disaster Jurisprudence), etc. On the basis of that considerations, this paper wants to answer some crucial questions; First, how exactly is Muhammadiyah's new fiqh reasoning and what is the difference between classical fiqh concept?; Second, where is the position of Muhammadiyah's new fiqh reasoning in the perspective of contemporary Islamic law studies that are developing, especially in the West ?; and Third, as a concept that produces ijtihad products, then there is a probability of Muhammadiyah's fiqh reasoning can become a new paradigm of Islamic law. The question is, how far is the probability?